Productivity, economics and energetics of wheat under different methods of crop establishment and irrigation schedules - Brar, A.S.; Mahal, S.S.; Deol, J.S.; Buttar, G.S. (Annals of Agricultural Research, 2014)
A field experiment was conducted to study the influence of methods of sowing and irrigation schedules on productivity, economics and energetics of wheat, during 2005-06 and 2006-07. The experiment was laid out in split-plot design, with three methods of crop establishment i. e. conventional, bed planting and zero-till in main plots and three irrigation schedules viz. 1.25, 1.00, and 0.75 IW:CPE in sub plots with four replications. The grain yield of wheat did not vary significantly with different methods of crop establishment. However, zero-till sowing was found to be more remunerative in terms of net returns, benefit: cost and specific energy over conventional and bed planting. Among the irrigation schedules maximum grain yield (48.2 q/ha) was obtained when irrigation applied at 1.25 IW: CPE, which was statistically at par with 1.0 IW: CPE (46.8 q/ha), but both were significantly better than irrigation applied at 0.75 IW: CPE (43.7 q/ha). Similar trend was observed for net returns and benefit: cost, while reverse was true for economic water productivity. Maximum energy output (70854 MJ/ha) was recorded with irrigation scheduling at 1.25 IW: CPE followed by 1.0 (68796 MJ/ha) and least in 0.75 (64239 MJ/ha) IW: CPE. However, energy input was the lowest (12225 MJ/ha) in irrigation schedule of 0.75 IW: CPE, which was 18.8 and 13.8 per cent less than irrigation schedules of 1.25 and 1.0 IW: CPE, respectively.